Pengembangan Perangkat Pembelajaran Fisika Berorientasi Pada Kreativitas Calon Guru - Hairunnisyah Sahidu; Gunawan Gunawan; Joni Rokhmat; Satutik Rahayu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
Learning tools are an important part of learning. Innovative learning tools will help lecturers and students achieve the goals in learning. The purpose of this research is to produce an innovative learning tools oriented to the creativity of preservice physics teachers. The type of research is development research, using DDD-E model: decide, design, develop, and evaluate. Instruments used include physics concept test with multiple choice form, essay-type creativity test, activity observation sheet in Likert scale questionnaire. In this study also conducted empirical testing to measure the effectiveness of learning tools which developed to increase student creativity. The results show that the highest creativity improvement of the experimental class on verbal creativity.